Development of an E-Module as a Differentiated Learning Resource to Enhance Junior High School Students’ Mathematical Conceptual Understanding - Putu Nesya Pundiwanti; Ni Made Sri Mertasari; Raphita Yanisari Silalahi (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
This study was motivated by students’ low mathematical conceptual understanding and the need for learning resources capable of accommodating diverse learning styles through differentiated learning. The study aimed to develop a differentiated statistics e-module that is valid, practical, and effective in improving students’ mathematical conceptual understanding. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The participants included 32 eighth-grade students and two mathematics teachers at SMPN Satu Atap 2 Sukasada. Data were analyzed descriptively using quantitative criteria covering validity, practicality, and effectiveness. The validity of the e-module was evaluated using the LORI instrument by material and media experts, while practicality was measured through teacher and student response questionnaires. Effectiveness was determined based on pretest and posttest results analyzed using the N-Gain method. The findings revealed that the developed e-module was categorized as highly valid, with scores of 4.90 from material experts and 4.76 from media experts. The practicality of the e-module was also categorized as highly practical, with scores of 4.75 from teachers and 4.43 from students. The N-Gain score of 0.71 indicated a high effectiveness category. These findings demonstrate that the differentiated statistics e-module is feasible as a learning resource to improve students’ mathematical conceptual understanding.